Electrochemical reduction of porous vanadium trioxide precursors in molten fluoride salts. (10th February 2018) - Kong, Yapeng; Chen, Jianshe; Li, Binchuan; Liu, Kuiren; Han, Qing
Abstract: The mechanism of the electrochemical reduction of vanadium trioxide (V2 O3 ) towards the formation of metallic vanadium in molten NaF-AlF3 salts was investigated by cyclic voltammetry and constant potential electrolysis. The porous V2 O3 precursors were prepared from ammonium polyvanadate through coal gas reduction and sintering. The cathodic products were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM) and energy dispersive spectrometer (EDS). The results indicated that the direct electrochemical reduction of V2 O3 and aluminothermic reduction reaction both occurred during the reduction of V2 O3, and the latter played a key role. A rapid electro-reduction of V2 O3 was achieved, through which the oxygen content of the formed metallic vanadium decreased to 0.216 mass% after 4 h of electrolysis. The oxygen removed from the V2 O3 cathode partly transported to the carbon anode in the form of Al–O–F complex ions, and partly existed in the form of aluminum oxide, which was then electrolyzed to realize the circulation of aluminum in the system. Highlights: Porous vanadium trioxide cathode was prepared from ammonium polyvanadate precursor. NaF-AlF3 molten salts were used to realize rapid reduction of V2 O3 to vanadium. The reduction mechanism and reaction pathway of vanadium trioxide were discussed. Both electro-reduction and aluminothermic reduction occurred during the process.